Strategic Factor Market Intelligence: An Application of Information Economics to Strategy Formulation and Competitor Intelligence - Makadok, Richard; Barney, Jay B. (Management Science, 2001)
This paper develops a model of information-acquisition decisions by firms that are competing in a “strategic factor market” (Barney 1986) to purchase a scarce resource whose value is unknown and differs across firms. The model builds on the argument that more accurate expectations about the firm-specific value of resources is, other than luck, the only way for firms to obtain the specific resources required for competitive advantage. We address the more specific question of what types of information firms should gather to accomplish this goal. The model generates a series of testable hypotheses about how a firm's optimal mix of different types of information is affected by a number of factors, including the level of uncertainty about the value of the resource being acquired; the rarity, imitability, and nonsubstitutability of that resource; the level of inscrutability of firms' pre-existing stocks of resources; and firms' information-gathering and information-processing capacities.